Soil Erosion - Venkatachari, AR (Journal of Soil and Water Conservation, 2022)
THE problem of soil erosion is an old one. Many areas which at one time were very fertile are at present barren with numerous gullies and erosions in many places in India. In the Oxford Pamphlets Series of Indian Affairs is Pamphlet No. 23 on Soil Erosion by Sir Harold Glover in which the causes, effects and remedies for soil erosion have been described in relation to the several forest areas of India with their differing local characteristics. A large amount of work has been done on soil erosion in the United States by the Soil Conservation Service under the United States Department of Agriculture. An attempt at describing in one volume the various methods adopted in various places in dealing with soil erosion in India and other countries has been made in the publi-cation of the Government of Madras " Soil Erosion — Its Prevention and Control ". This note is intended to focus attention on salient features ui Lti1a pi vuLt-iii, 4. 4./ %an. v ... a “■ _ the more important remedies to be applied wherever such erosion has caused serious damage, and to describe steps necessary to prevent erosion spreading to new areas.